1996
DOI: 10.1075/sl.20.1.02ada
|View full text |Cite
|
Sign up to set email alerts
|

Sarcasm in Japanese

Abstract: Various kinds of motivation, such as psychological and physiological, affect and determine the forms of an utterance. Often observed consistent forms of sarcastic expression are likewise configured by sarcastic motivations. These forms, though still reflecting their original sarcastic motivation, progressively become emancipated from that motivation and become increasingly rigid and arbitrary as they undergo repetition. The relationships between motivation, this process of "grammaticalization", and arbitrary l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 0 publications
5
17
0
1
Order By: Relevance
“…The finding that sarcasm is produced with less amplitude variation ͑range͒ in Cantonese, and frequently with a slower speech rate, coincides with data on English and other languages such as Japanese, Italian, and French ͑e.g., Adachi, 1996;Anolli et al, 2002;Bryant and Fox Tree, 2005;Laval and Bert-Erboul, 2005;Rockwell, 2000a͒. It has been suggested that a reduced speech rate has the effect of drawing listener focus to a particular excerpt of discourse for a number of communicative purposes ͑Haiman, 1998; Kreuz and Roberts, 1995͒.…”
Section: ͒mentioning
confidence: 99%
“…The finding that sarcasm is produced with less amplitude variation ͑range͒ in Cantonese, and frequently with a slower speech rate, coincides with data on English and other languages such as Japanese, Italian, and French ͑e.g., Adachi, 1996;Anolli et al, 2002;Bryant and Fox Tree, 2005;Laval and Bert-Erboul, 2005;Rockwell, 2000a͒. It has been suggested that a reduced speech rate has the effect of drawing listener focus to a particular excerpt of discourse for a number of communicative purposes ͑Haiman, 1998; Kreuz and Roberts, 1995͒.…”
Section: ͒mentioning
confidence: 99%
“…Conversely, Rockwell (2000) found that a higher pitch was a marker of irony. Adachi (1996) reports that an exaggerated pitch marks irony; this is similar to Schaffer's (1981) were used as markers of irony. The use of a marked succession of prominent syllables is analyzed as "beat clash" by Uhmann (1996), and is argued to provide a cue to irony.…”
Section: Phonological Markersmentioning
confidence: 99%
“…There seem to be definite differences across languages: see Adachi (1996) for Japanese, Anolli et al (2002) for Italian, Laval and Bert-Erboul (2005) Bertrand and Priego-Valverde (this issue) for French, and Cheang and Pell (this issue), for Cantonese Chinese. There are also differences across age groups: Capelli et al (1990), Milosky and Ford (1997), and Laval and Bert-Eboul (2005) note that younger children rely more on prosodic cues.…”
Section: Conclusion Of the Above Discussionmentioning
confidence: 94%
“…Similarly, Haiman discusses "inverse pitch obtrusion" (i.e., the utterance of the stressed syllable "at a lower pitch than the surrounding material" 1998: 31) in English and German. Muecke (1978: 370-371), Schaffer's (1981), Adachi (1996), and Haiman (1998) report that an exaggerated pitch or extremes of pitch marks irony. Similarly, Attardo et al (2003) claim that "exaggerated pitch marks sarcasm".…”
Section: Phonological Markersmentioning
confidence: 95%